Pelaksanaan Budaya Sekolah Di Sekolah Dasar - Sinta Febrianti; Wahira Wahira; Sitti Habibah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The focus of this research is how to describe the implementation of school culture and what are the supporting and inhibiting factors. This study aims to describe how the implementation of school culture is described and describe the supporting and inhibiting factors for the implementation of school culture in SD Muhammadiyah I Layang Parang Layang Makassar City. This research uses a qualitative approach, therefore in order to obtain a research objective, data collection methods are used, namely interviews, observations and documentation. The data sources in this study are principals, teachers and students at SD Muhammadiyah I Layang Parang (LP) Layang Makassar City. Data analysis in this study is data reduction, data presentation and conclusion drawn. The results of this study show that the implementation of school culture in SD Muhammadiyah I Layang Parang (LP) Layang Makassar City is identified through values, beliefs and habits. The values applied are the values of honesty, discipline, and social concern. The beliefs in SD Muhammadiyah I Layang Parang (LP) Layang Makassar City are related to Islamic values, namely Tawhid and Akhlak. Then the habits applied are the habit of praying before and after studying, Friday prayers in congregation, cleaning the classroom environment, and weekly infaq. The supporting factors for the implementation of school culture at SD Muhammadiyah I Layang Parang (LP) Layang Makassar City are the participation of teachers, the integration of Islamic values into learning and activities that have been programmed. There are factors that hinder the implementation of school culture at SD Muhammadiyah I Layang Parang Layang Makassar City including inadequate facilities, lack of parental involvement, and lack of support from friends.